Narrowing the Gap: An Implementation Science Research Agenda for the Occupational Therapy Profession. - Juckett, Lisa A.; Robinson, Monica L.; Wengerd, Lauren R. (American Journal of Occupational Therapy)
Despite advancements in occupational therapy research, the widespread research-to-practice gap continues to delay how quickly evidence-based practices are implemented in real-world clinical settings. Implementing research in practice is a complex process that mandates attention from all occupational therapy stakeholders; however, researchers are uniquely positioned to help minimize the 17-yr lag between scientific discovery and the implementation of research findings into practice. Our article serves as a response to Marr's (2017) Centennial Topics article, which proposed that purposeful efforts are needed to advocate for implementation research in occupational therapy. We provide an implementation science research agenda informed by concepts from the implementation science literature and suggest how researchers can structure methodologies to examine implementationrelated outcomes and strategies. We provide explanations of gold-standard implementation outcomes and offer several recommendations for how researchers can report and disseminate implementation research findings to occupational therapy stakeholders.